TAMANSARI MONGSO RENDHENG KARYA HENDRO MARTONO DAN BAGHAWAN CIPTONING KAJIAN KONSEP KOREOGRAFI LINGKUNGAN - Lilin Candrawati Sukmaningsih (SURYA SENI, 2008)
The research is aimed to determine, examine, and analyze an  Architectural Choreography of Hendro Martono and Baghawan Ciptoning’s Tamansari Mongso Rendheng (TMR) presented on 1 and 2 March 2003 in Tamansari Keraton Yogyakarta. Conceptual Study on Choreography of TMR is a qualitative research conducted on November – June 2006. Data collecting techniques employed in the research were interview,  observation, documentary study, and literaturestudy. Interview was conducted by directly asking questions to choreographers, artists, educational workers watching TMR, and the society around Tamansari.Observation was conducted by directly observing the TMR. Documentary study was regularly conducted through video record of TMR. Literature Study was conducted by reading documents relating TMR and literature on choreography. Results of the research show that: First, TMR choreography is an  architectural choreography resulted by movement and sound exploration in a room of old building offering new discourse in efforts to ﬁ ll and to bring to life ancient architecture through cultural behavior. Choreographic concept of TMR was conducted by observing Tamansari and its environment through  choreography not only as entertainment, but also choreography as  multifunction not only a dance performance but also a learning model for history, architecture, tourism, culture, sociology, and modern transformation. Second, the creation process of TMR included: experiencing, comprehending, imagining,  implementing, and giving forms.  TMR is divided into eight presentations of each repertoire as follow: 1) Gapura Panggung: photographs exhibition, 2) Gedong Sekawan: keroncong music, Glass Srimpi, Flamenco, Waltz, ﬂ ash of past period,  Dagelan Parikeno, 3) Umbul Binangun: Srimpen Lelumban, 4) Pasarean Ledhoksari:the servant’s (abdi) activities in well, Kamasutra, and Ngadi Sarira, 5) Gapura Agung: Isen-isene Jagad, 6) Kampung Taman: real life of the society, 7) Sumur Gumuling: Donga Joged, and 8) Urung-urung: self-contemplation of the onlookers after enjoying TMR.Keywords: Choreography, Architectural, Tamansari Environment, and Mangsa Rendheng